2021
DOI: 10.1186/s13195-021-00900-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods for predicting progression from mild cognitive impairment to Alzheimer’s disease dementia: a systematic review

Abstract: Background An increase in lifespan in our society is a double-edged sword that entails a growing number of patients with neurocognitive disorders, Alzheimer’s disease being the most prevalent. Advances in medical imaging and computational power enable new methods for the early detection of neurocognitive disorders with the goal of preventing or reducing cognitive decline. Computer-aided image analysis and early detection of changes in cognition is a promising approach for patients with mild cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 139 publications
4
84
0
Order By: Relevance
“…Besides augmenting our understanding of AD pathophysiology, new measures of altered hippocampal activity could aid in developing stronger prognostic and/or diagnostic markers, since current EEG/MEG-based markers lack specificity [ 3 ]. However, larger groups, longitudinal data, multimodal data, and machine-learning based approaches may be required [ 75 ]. So far, relatively straightforward measures such as spectral power perform best, so using them to look at specific regions or conditions may be an equally valid approach.…”
Section: Discussionmentioning
confidence: 99%
“…Besides augmenting our understanding of AD pathophysiology, new measures of altered hippocampal activity could aid in developing stronger prognostic and/or diagnostic markers, since current EEG/MEG-based markers lack specificity [ 3 ]. However, larger groups, longitudinal data, multimodal data, and machine-learning based approaches may be required [ 75 ]. So far, relatively straightforward measures such as spectral power perform best, so using them to look at specific regions or conditions may be an equally valid approach.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed in order to identify specific anatomical regions associated with cognitive test performance, rather than develop a diagnostic tool. Nonetheless, many studies utilizing machine learning have reported excellent performance, with accuracy, sensitivity and specificity at times exceeding 99% ( Odusami et al, 2021 ), though a recent systematic review demonstrated a mean accuracy of 75.4% for support vector machines in predicting progression of MCI to AD ( Grueso and Viejo-Sobera, 2021 ). However, a primary reason preventing the implementation of these models in clinical practice is their replicability, where the same models which have often overfitted to the study sample will underperform with independent data sets ( Beam et al, 2020 ; Crowley et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the advancement of machine learning algorithms and new data, we have the opportunity to analyze large data sets and build prediction models to inform clinical practice ( Panch et al, 2018 ; Davenport and Kalakota, 2019 ). Various studies have utilized machine learning to predict the conversion of MCI to AD based on neuropsychological measures and clinical markers, with several studies focusing on neuroimaging models ( Huang et al, 2020 ; Stamate et al, 2020 ; Syaifullah et al, 2020 ; Grueso and Viejo-Sobera, 2021 ). Wee et al (2012) employed support vector machines to demonstrate that a multimodal approach combining functional and structural connectivity data improved the accuracy of MCI classification.…”
Section: Introductionmentioning
confidence: 99%
“…While the challenges using ADNI for testing took measures to limit the advantage of researchers being more familiar to the data, the challenge results may still be biased towards its specific data characteristics. Data from the ADNI plays a major role in the research field of machine learning in Alzheimer's disease and is used for optimization and validation in 60 − 90% of the published articles (Rathore et al, 2017;Grueso and Viejo-Sobera, 2021). Therefore, state-of-theart performance in ADNI is likely to be an overestimation of performance in clinical practice.…”
Section: Clinical Impactmentioning
confidence: 99%